A Perspective on Working in Hospice and Grief - Lindsey Ingle (Palliative Medicine and Hospice Care, 2020)
Almost every time that I share my profession with others, I am met with a myriad of facial expressions and awkward ges-tures that reflect a sort of discomfort and general misunderstand-ing about what I do. The only common thread in public perception seems to be that it’s hard and terribly sad.